The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1755-3768.2010.369.x
|View full text |Cite
|
Sign up to set email alerts
|

Angle configuration changes after phacoemulsification measured with anterior segment optical coherence tomography (AS OCT)

Abstract: Purpose To assess the changes of the irio corneal angle configuration and anterior chamber depth with anterior segment optical coherence tomography (AS OCT) after phacoemulsification. Methods Prospective study including consecutive patients operated on age related cataract with phacoemulsification and intraocular lens implantation. An AS OCT was performed before and one month after cataract surgery on the horizontal meridian. The primary objective was to assess the changes of AC depth, iridocorneal angle, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Preoperative AOD and TISA were also significant predictors of reduction of IOP (p < 0.01 and p < 0.001). Bron et al [ 23 ] concluded that pre-operative TISA 500 and AOD 500 were predictors of post-operative reduction in IOP, which agrees with our study’s results.…”
Section: Discussionsupporting
confidence: 93%
“…Preoperative AOD and TISA were also significant predictors of reduction of IOP (p < 0.01 and p < 0.001). Bron et al [ 23 ] concluded that pre-operative TISA 500 and AOD 500 were predictors of post-operative reduction in IOP, which agrees with our study’s results.…”
Section: Discussionsupporting
confidence: 93%